Levels and targeting of social benefits in global perspective: Combatting poverty through social policy - Tommy Ferrarini; Kenneth Nelson; Joakim Palme (Luxembourg Income Study (LIS), 2015)
This study investigates an old question that has re-emerged in social policy-making and in analyses of global social development: to what extent does targeting and size of social transfers matter for poverty? Using multilevel logistic regression and LIS income data for 40 middle- and high-income countries, we show that the size of transfer income has greater explanatory value for cross-country differences in poverty than the degree of targeting of transfer income. The results are remarkably robust in terms of estimated individual-level and country-level compositional and confounding factors.
Keywords: 330